Identification and phylogenetic analysis of Jingmen tick virus in ticks and sheep from Henan Province, China - Baicheng Xia; Zhenhua Li; Wenbing Zhu; Zhen Wu; Yuli Zhang; Yujing Zhu; Hengyi Sun; Guoyu Niu (Virology Journal, 2024)
Abstract Jingmen tick virus (JMTV) is a novel segmented Flavivirus that was first identified from Rhipicephalus microplus in the Jingmen region of Hubei Province, China, in 2010. Subsequently, it was detected in a variety of countries and regions around the world. Meanwhile, JMTV has been proved to be pathogenic to humans and animals and could cause viremia in animals. However, the pathogenic mechanism of JMTV and what role animals play in the viral cycle have not yet been elucidated. In this study, 38 sheep sera were collected from Xinyang region of Henan Province, China and 204 ticks attached to the sheep were collected. The qRT-PCR and nested PCR were used to confirm the presence of JMTV in serum and tick samples. The results showed that the positive rate of JMTV in serum and ticks was 13.16% (5/38) and 7.84% (16/204), respectively. Phylogenetic analysis showed that JMTV sequences in sheep and ticks shared a high degree of identity with each other, and JMTV was relatively conserved in evolution. These results enriched the evidence for the prevalence of JMTV in animals and further deepened our understanding of the mechanisms and routes of JMTV transmission.